Phytosterol intake and overall survival in newly diagnosed ovarian cancer patients: An ambispective cohort study - Zhao, Jun-Qi; Hao, Ying-Ying; Gong, Ting-Ting; Wei, Yi-Fan; Zheng, Gang; Du, Zong-Da; Zou, Bing-Jie; Yan, Shi; Liu, Fang-Hua; Gao, Song; Wu, Qi-Jun; Zhao, Yu-Hong (Frontiers in Nutrition, 2022)
Background: Phytosterol is a bioactive compound existed in all plant foods, which might have anticancer properties. The purpose of this study was to firstly evaluate the impact of the pre-diagnosis phytosterol intake on overall survival (OS) of OC patients. Methods: This prospective cohort study recruited 703 newly diagnosed OC patients to investigate the aforementioned associations. Dietary intake was assessed using a validated 111-item food frequency questionnaire. Deaths were ascertained until March 31, 2021, through active follow-up and medical records. Cox proportional hazards regression models were applied to calculate the hazard ratios (HRs) and 95% confidence intervals (CIs). Results: During the median follow-up of 37.17 months, 130 deaths occurred. Patients consumed the highest tertile of dietary campesterol (HR = 0.54, 95% CI = 0.31-0.94, P trend < 0.05), stigmasterol (HR = 0.60, 95% CI = 0.37-0.98), and β-sitosterol (HR = 0.63, 95% CI = 0.40-0.99) were significantly associated with better OS compared with those with the lowest tertile of intake. The curvilinear associations were observed between total phytosterols and β-sitosterol intake and OC survival (P non-linear < 0.05). Significant associations were generally consistent across different subgroups stratified by demographical, clinical, and immunohistochemical characteristics. Moreover, there were significant interactions between phytosterol intake and age at diagnosis, body mass index, as well as Wilms’ tumor-1 and Progestogen Receptor expressions (all P interaction < 0.05). Conclusion: Our study suggested that pre-diagnosis higher campesterol, stigmasterol, and β-sitosterol intake were associated with better survival of OC patients.